-3=-5-2y

Simple and best practice solution for -3=-5-2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=-5-2y equation:


Simplifying
-3 = -5 + -2y

Solving
-3 = -5 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-3 + 2y = -5 + -2y + 2y

Combine like terms: -2y + 2y = 0
-3 + 2y = -5 + 0
-3 + 2y = -5

Add '3' to each side of the equation.
-3 + 3 + 2y = -5 + 3

Combine like terms: -3 + 3 = 0
0 + 2y = -5 + 3
2y = -5 + 3

Combine like terms: -5 + 3 = -2
2y = -2

Divide each side by '2'.
y = -1

Simplifying
y = -1

See similar equations:

| (b+2)x(b-3)= | | -8y-3=7y-6 | | 17-(4x-6)=58 | | 0=r-16 | | 9k^2+9k+1=0 | | 1/4(9+2x)=19 | | -1=-x/4-6 | | 6(x-1)+8=4x+2(-1+x) | | 9n^2+4n=0 | | -4(1)+8=8 | | -8=11+k | | X+2y-12=0 | | (ln)x+(ln)x^2=6 | | -3/4x=-21 | | 4(2x-3)-4x=3(2x-6) | | 86=21-13x | | 2x+19=5x+4 | | 4(2x-3)-4x=3x-4 | | x(x+3)=(x-2)(x-4) | | 4(2x-3)-4x=4x-12 | | 6w^2-1=0 | | 2900-p=64 | | 2x^2+16x+32=24 | | 12x-44=7x+13 | | 2x-3yi=-14+9i | | .36(12)+.06x=.18(12+x) | | 7z^2-7z+1=0 | | 5y-[-(2-3y)+4]=-9y-[-(1+4y)-8]+2 | | Y-2714=3601 | | -16=n-16 | | 48-5/4 | | 8f^2-8=0 |

Equations solver categories